Training in Progress. Communication Skills and Cultural Background of Italian Journalists - Buoncompagni, Giacomo (Italian Sociological Review, 2025)
This article investigated the relationship between media and justice, between journalists and jurists, in relation to hate crimes and their hidden forms, focusing on anti-Semitism, the main subject of the research. Favouring a socio-cultural perspective of the phenomenon, after a short theoretical parenthesis (concerning the study of national and international literature on the topic of anti-Semitism and the contemporary media system), the paper will present the results of focus groups addressed to participants belonging to two different categories of publics: freelance and professional journalists and Italian lawyer-magistrates. The analysis focuses on the professionalism and responsibility of journalists and jurists in dealing with anti-Semitic phenomena and hate in general. Specifically, the study will investigate the journalistic culture in relation to the phenomenon of anti-Semitism, taking into account the complexity and ‘gaps’ of criminal law in Italy regarding hate news.